Letting go of the words : writing web content that works - Redish, Janice (Morgan Kaufmann, 2012)
Web site design and development continues to become more sophisticated an important part of this maturity originates with well laid out and well written content. Ginny Redish is a world-renowned expert on information design and how to produce clear writing in plain language for the web. All of the invaluable information that she shared in the first edition is included with numerous new examples. New information on content strategy for web sites, search engine optimization (SEO), and social media will enhance the book's content making it once again the only book you need to own to optimize your writing for the web. New material on content strategy, search engine optimization, and social media. Lots of new and updated examples. More emphasis on new hardware like tablets, iPads, and iPhones.